Single-Site Nissen Fundoplication Versus Laparoscopic Nissen Fundoplication - Sharp, Nicole E. (Society of Laparoendoscopic Surgeons, 2014)
BACKGROUND: Advances in minimally invasive surgery have led to the emergence of single-incision laparoscopic surgery (SILS). The purpose of this study is to assess the feasibility of SILS Nissen fundoplication and compare its outcomes with traditional laparoscopic Nissen fundoplication. METHODS: This is a retrospective study of 33 patients who underwent Nissen fundoplication between January 2009 and September 2010. RESULTS: There were 15 SILS and 18 traditional laparoscopic Nissen fundoplication procedures performed. The mean operative time was 129 and 182 minutes in the traditional laparoscopic and single-incision groups, respectively (P = .019). There were no conversions in the traditional laparoscopic group, whereas 6 of the 15 patients in the SILS group required conversion by insertion of 2 to 4 additional ports (P = .0004). At short-term follow-up, recurrence rates were similar between both groups. To date, there have been no reoperations. CONCLUSIONS: SILS Nissen fundoplication is both safe and feasible. Short-term outcomes are comparable with standard laparoscopic Nissen fundoplication. Challenges related to the single-incision Nissen fundoplication include overcoming the lengthy learning curve and decreasing the need for additional trocars.